2022
DOI: 10.3892/etm.2022.11569
|View full text |Cite
|
Sign up to set email alerts
|

Citrulline protects against LPS‑induced acute lung injury by inhibiting ROS/NLRP3‑dependent pyroptosis and apoptosis via the Nrf2 signaling pathway

Abstract: Acute lung injury (ALI) is a common complication in patients with sepsis and is accompanied by high mortality. The present study aimed to investigate if the organic compound citrulline has a protective against lipopolysaccharide (LPS)-stimulated ALI and its potential mechanisms. ALI was induced in mice by intraperitoneal (i.p.) injection of LPS (10 mg/kg). Citrulline (1 g/kg/day) was administrated i.p. 7 days prior to LPS injection. Mouse lung vascular endothelial cells (MLVECs) were divided into five groups: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…It is reported to possess anti‐inflammatory effects by suppressing pyroptosis. A previous study has revealed that citrulline inhibits pyroptosis, apoptosis, and inflammatory changes induced by LPS in lung 19 . Consistently, the results in this study indicated that citrulline promoted LPS‐induced cell viability and suppressed pyroptosis of RAW264.7 cells.…”
Section: Discussionsupporting
confidence: 91%
“…It is reported to possess anti‐inflammatory effects by suppressing pyroptosis. A previous study has revealed that citrulline inhibits pyroptosis, apoptosis, and inflammatory changes induced by LPS in lung 19 . Consistently, the results in this study indicated that citrulline promoted LPS‐induced cell viability and suppressed pyroptosis of RAW264.7 cells.…”
Section: Discussionsupporting
confidence: 91%
“…We also observed a difference in the ASC amount between cell lines, but a higher ASC amount was not associated with more ASC speck formation. A high expression of ASC protein is often used as a marker for inflammasome formation in multiple types of cancer [21,31,[43][44][45][46][47][48][49]. The ASC protein levels [13] and PYCARD gene expression [50] (Figure 5e) were increased in the PDAC tissue, but our results imply that the ASC amount alone may be a poor marker for inflammasome formation.…”
Section: Discussionmentioning
confidence: 65%
“…Moreover, recent studies have revealed that high-mobility group box 1 (HMGB1) can also activate Caspase-1 in hemorrhagic shock-induced ALI, thus amplifying LPS-triggered endothelial cell pyroptosis ( Yang et al, 2016 ). Secondly, in terms of pharmacological interventions, beyond metformin, small molecule compounds like Isopropyl 3-(3,4-dihydroxyphenyl)-2-hydroxypropanoate—one of the primary bioactive metabolites of the Chinese medicinal herb Danshen—and Citrulline have shown promise in reducing endothelial cell pyroptosis by inhibiting NLRP3 activity ( Xue et al, 2022 ; Zhang ML. et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%